TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH ATAS OBJEK PALSU YANG MENJADI DASAR PEMBUATAN AKTA JUAL BELI DAN KEKUATAN PEMBUKTIAN AKTA TERSEBUT (STUDI KASUS PUTUSAN PENGADILAN TINGGI BADUNG NOMOR: 451/PDT/2015.PT.BDG) - HARIYADI HARIYADI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. Notaris Suprayitno3. Madiasa Ablizar One of the negligence cases about false object was given by the personsappearing who want to make sales deeds in the Bandung Appellate Court’s VerdictNo. 451/PDT/2015.PT.BDG. PPAT did negligence in making the contract a SalesDeed No. 250/2012 on June 19, 2012 and a Sales Deed No. 251/2012 on June 19,2012 because the buyer had given false object. The research conclusion is that the legal domicile and the evidence of thesales deeds made by PPAT which contain false object cause them to be degradedinto underhanded certificates and can be revoked. A PPAT who makes an authenticdeed which contains false object can be imposed with administrative and civilsanction. It is recommended that a PPAT be guided by the prevailing laws andregulations on sales deeds and in making sales contracts. Keywords: PPAT’s Liability, False Object, Sales Deeds